Familial and sporadic hyperinsulinism: Histopathologic findings and segregation analysis support a single autosomal recessive disorder - Thornton, Paul S.; Sumner, Anne E.; Ruchelli, Eduardo D.; Spielman, Richard S.; Baker, Lester; Stanley, Charles A. (The Journal of pediatrics, 1991)
We evaluated the possible genetic contribution to hyperinsulinism in a series of patients seen during the past 15 years. Of 26 families, 5 (19%) had more than one child affected (multiplex family). There were no apparent differences between patients in the 5 multiplex and 21 simplex families, clinically, biochemically, or on histologic examination of the pancreatic specimens. The families studied had a total of 63 offspring; the 26 index patients had 37 siblings, 6 of whom were affected. After four patients with hyperinsulinism caused by adenoma were excluded from the study, segregation analysis was carrled out to test the data for agreement with results expected if familial and isolated hyperinsulinism represented a single disease with recessive mode of inheritance and a segregation ratio of 0.25. Excellent agreement was found between the observed number of affected siblings (20) and the expected number (19.65), with a segregation ratio of 0.254. The results were consistent with the hypothesis that in most or all cases, hyperinsulinism is inherited as an autosomal recessive disease. There was no evidence of distinct familial and sporadic types.